Thoracic surgeryThoracoscopy in the treatment of spontaneous pneumothorax in children - Grabowski, Andrzej; Korlacki, Wojciech; Pasierbek, Michał; Achtelik, Filip (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Spontaneous pneumothorax occurring in children is routinely treated in a conservative manner. An important clinical problem is to find solutions for patients with persistent or recurrent pneumothorax. The surgery previously executed with classic thoracotomy is now performed with thoracoscopic access. The aim of this study was to analyze the effectiveness of thoracoscopic interventions in children with spontaneous pneumothorax. Material and methods: The work was based on a retrospective evaluation of the records of 46 patients operated on for spontaneous pneumothorax in the years 1997-2012. The assessment takes into account patient demographics, length of hospital stay, and the type of surgical procedure. The immediate and long-term postoperative period was followed, with particular attention paid to pathology recurrence. Results: In the years 1996-2011, 46 patients (11 girls and 35 boys) were treated surgically for spontaneous pneumothorax. The average age was 15.48 years (range: 11-18 years), mean weight – 58.7 kg (range 33-76 kg). 52 thoracoscopic procedures were performed in 46 patients. In 5 patients, interventions for recurrent pneumothorax on the opposite side were necessary. Time of hospital stay after surgery ranged from 3 to 33 days (average of 7.35). There were no deaths. Complications during hospitalization occurred in 8 patients (17.4%). Conclusions: Minimally invasive thoracoscopic intervention in the case of spontaneous pneumothorax in children is an effective and safe method of treatment. It is burdened with negligible risk of recurrence, which reduces the exposure of the child to repeated thoracocenteses or drainage of the pleural cavity.